Impact of Work From Home Policy on Behavior and Productivity of Lecturers and Education Staff - Afni Sirait; Sri Luna Murdianingrum (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2021)
Policy Work From Home (WFH ) is enforce within the FEB UPN "Veteran" Yogyakarta is one manifestation of breaking the chain of the COVID-19 virus. This research purpose is to identify the influence of WFH on the behavior and productivity of lecturers and education staff during this policy. This research is something new in education. The productivity assessment of the implementation of this policy has never be analyzed. This study uses quantitative methods with the number of respondents 96 respondents. The data was collected using a questionnaire, then tested the validity, reliability, and evaluation of the model structure using data analysis tools SmartPLS 3.0.0. The results of data processing explained that there was no relationship between WFH and technology-mediated behavior (P-Value = 0.297; T-Statistic = 1.043). A different yield of WFH data processing with productivity. It was found positive and significant influence but mediated partially competitive by technology. The path coefficient value of the direct relationship between WFH and productivity is 0.206 (P-Value 0.034; T-Statistic = 2.132) that the indirect relationship between WFH and productivity is mediating by the technology of 0.353. The limitation of this research is that it is only carried out in the FEB environment, not yet in a comprehensive manner at the “Veteran” National Development University, Yogyakarta.